High-density strong-insulation super-thick carbon-doped ceramic coating and preparation method thereof

By depositing a base layer, a carbon-based intermediate layer and a ceramic surface layer on the metal substrate, a high density and strong insulation ultra-thick carbon-doped ceramic coating is prepared, which solves the problems of insufficient coating thickness and complex preparation methods in the prior art, and realizes a high-performance ceramic coating.

CN119615079AActive Publication Date: 2025-03-14CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411749029.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The total thickness of the ultra-thick carbon-based composite coating prepared by magnetron sputtering technology in the prior art is only 26μm. The preparation method is complicated and cannot achieve ultra-thickness, high density, high insulation, high bonding strength and high wear resistance.

Method used

By depositing a Ti/TiC or Cr/CrN base layer on the substrate, then depositing a carbon-based intermediate layer, and depositing a C/SiO2/Al2O3 ceramic surface layer thereon, a high density and strong insulation ultra-thick carbon-doped ceramic coating is formed.

Benefits of technology

The total thickness of the ceramic coating is achieved to reach 40-60μm, the insulation strength is 700-1100MΩ, the binding force is 25-40N, the hardness is 600-1000HV, and the film layer is intact after 3000 hours of salt spray corrosion test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615079A_ABST
    Figure CN119615079A_ABST
Patent Text Reader

Abstract

The invention provides a high-density and strong-insulation super-thick carbon-doped ceramic coating and a preparation method thereof. The preparation method comprises the following steps: S1, substrate pretreatment, wherein the pretreatment sequentially comprises polishing and chemical cleaning; s2, plasma sputtering cleaning is carried out; s3, depositing a base layer; the base coat is a Ti / TiC base coat or a Cr / CrN base coat; the thickness of the base layer is 0.2 to 0.8 [mu] m; s4, depositing a carbon-based middle layer on the base layer; the thickness of the carbon-based intermediate layer is 2-10 [mu] m; s5, depositing a C / SiO2 / Al2O3 ceramic surface layer on the carbon-based intermediate layer; and the thickness of the C / SiO2 / Al2O3 ceramic surface layer is 10 to 50 [mu] m. The total thickness of the prepared coating can reach 45-60 microns, and the coating has high compactness, high insulativity, high binding force and high wear resistance; and the preparation method is simple, and the ceramic coating can be obtained only by depositing three layers on the base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface treatment, and in particular to a highly dense and highly insulating ultra-thick carbon-doped ceramic coating and a preparation method thereof. Background Art

[0002] Titanium alloy, stainless steel, aluminum alloy and other metal materials are widely used in marine ships, aerospace, petrochemical and other fields. However, in some harsh corrosive environments, the surface of metal materials will suffer from serious corrosion problems. In addition, when dissimilar metal parts are assembled and contacted, there is a large potential difference, which leads to galvanic corrosion. Material corrosion poses a serious threat to the safety and reliability of components, and may cause accidents and economic losses. Therefore, the insulation and anti-corrosion technology of metal material surface is crucial to the development of various fields.

[0003] The prior art with application number CN202211572430.1 discloses an ultra-thick carbon-based composite coating with a heterogeneous multilayer structure and its preparation method and application, wherein the ultra-thick carbon-based composite coating comprises a transition layer and an alternating layer stacked layer sequentially formed on the surface of a substrate, wherein the alternating layer stacked layer is formed by alternating heterogeneous structure layers and amorphous carbon layers, wherein the heterogeneous structure layers comprise any one or a combination of two or more of MeC layers, MeN layers, and MeCN layers, and Me is selected from Cr, Ti, or W; the outermost layer of the ultra-thick carbon-based composite coating is an amorphous carbon layer. The prior art mainly has the following problems: (1) the use of magnetron sputtering technology requires the deposition of a multilayer structure, and the preparation method is relatively complicated; (2) the total thickness of the composite coating using magnetron sputtering technology is only 26 μm, and once damaged during long-term use, the substrate is easily corroded; (3) the composite coating cannot achieve ultra-thickness, high density, high insulation, high bonding strength, and high wear resistance. Summary of the invention

[0004] In view of this, the present invention aims to propose a highly dense and highly insulating ultra-thick carbon-doped ceramic coating and its preparation method. This is to solve the problem that the magnetron sputtering technology used in the prior art requires the deposition of a multilayer structure, and the preparation method is relatively complicated; the total thickness of the composite coating using the magnetron sputtering technology is only 26μm, and once damaged during long-term use, the substrate is easily corroded; the composite coating cannot achieve ultra-thickness, high density, high insulation, high bonding strength, and high wear resistance.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A method for preparing a highly dense and highly insulating ultra-thick carbon-doped ceramic coating comprises the following steps:

[0007] S1. Substrate pretreatment: the pretreatment includes polishing and chemical cleaning in sequence;

[0008] S2, plasma sputtering cleaning;

[0009] S3, depositing a base layer; the base layer is a Ti / TiC base layer or a Cr / CrN base layer;

[0010] S4, depositing a carbon-based intermediate layer on the base layer;

[0011] S5. Depositing a C / SiO2 / Al2O3 ceramic surface layer on the carbon-based intermediate layer.

[0012] The setting deposits a Ti / TiC base layer or a Cr / CrN base layer on the substrate to improve the film-base bonding strength between the ceramic surface layer and the substrate; the carbon-based intermediate layer is used to improve the substrate bearing capacity and act as a template to force the amorphous growth of the top carbon film; the C / SiO2 / Al2O3 ceramic surface layer deposited on the carbon-based intermediate layer has high insulation strength and can play a good insulation effect. The ultra-thick C / SiO2 / Al2O3 ceramic surface layer is used to prepare the ceramic coating, which can improve the corrosion and intrusion resistance of the entire ceramic coating.

[0013] Preferably, when the substrate is a titanium alloy, Ti / TiC is used as the base layer; when the substrate is stainless steel, aluminum alloy or other metal materials, deposited Cr / CrN is used as the base layer.

[0014] Furthermore, the thickness of the base layer is 0.2-0.8 μm, the thickness of the carbon-based intermediate layer is 2-10 μm, the thickness of the C / SiO2 / Al2O3 ceramic surface layer is 10-50 μm, and the total thickness of the ultra-thick carbon-doped ceramic coating is 45-60 μm.

[0015] This setting controls the thickness of the base layer, mainly to improve the bonding strength and corrosion resistance between the film layer and the substrate; controls the thickness of the middle layer to improve the substrate load-bearing capacity and serve as a template to force the amorphous growth of the top carbon film, thereby increasing the thickness of the ceramic surface layer; controls the thickness of the ceramic surface layer to improve its insulation performance.

[0016] Furthermore, step S3 specifically comprises using a titanium target or a chromium target as a sputtering raw material, argon as a sputtering gas, and methane or nitrogen as a reaction gas to deposit a Ti / TiC primer layer or a Cr / CrN primer layer on the surface of the substrate.

[0017] Further, in step S3, the argon flow rate is 30-35 sccm, the methane or nitrogen flow rate is 150-175 sccm, the voltage is -600 to -800 V, the current is 20 to 25 A, and the deposition time is 30 to 40 min.

[0018] Furthermore, step S4 specifically includes closing the titanium target or the chromium target, using argon as a sputtering gas, methane as a reaction gas, and hydrogen as a reaction gas to deposit a carbon-based intermediate layer on the base layer.

[0019] Further, in step S4, the furnace heating temperature is 160-220°C, the methane flow rate is 80-120sccm, the hydrogen flow rate is 320-800sccm, the power is 1200-1600W, the bias voltage is -800--1000V, the current is 10A, and the deposition time is 2-3h.

[0020] Furthermore, step S5 is specifically to use graphite target, aluminum target, silicon target as sputtering raw materials, argon as sputtering gas, oxygen as reaction gas, and adopt DC reactive sputtering process to deposit C / SiO2 / Al2O3 ceramic surface layer on the carbon-based intermediate layer.

[0021] Further, in step S5, the applied pulse bias is 10-20 kV, the pulse width is 20-30 microseconds, the pulse frequency is 150-200 Hz, the argon working pressure is 0.3-0.5 Pa, the oxygen flow rate is 30-50 sccm, and the deposition time is 10-20 hours.

[0022] Furthermore, the surface roughness of the substrate after polishing is less than 0.5 μm, and preferably, the surface roughness is 0.2-0.5 μm.

[0023] Compared with the prior art, the method for preparing a highly dense and highly insulating ultra-thick carbon-doped ceramic coating described in the present invention has the following advantages:

[0024] 1) The present invention deposits a Ti / TiC base layer or a Cr / CrN base layer on the substrate to improve the film-base bonding strength between the ceramic surface layer and the substrate; the carbon-based intermediate layer is used to improve the substrate load and to act as a template to force the amorphous growth of the top carbon film; the C / SiO2 / Al2O3 ceramic surface layer deposited on the carbon-based intermediate layer has high insulation strength and can play a good insulation effect. The ultra-thick C / SiO2 / Al2O3 ceramic surface layer is used to prepare a ceramic coating, which can improve the corrosion resistance of the entire ceramic coating.

[0025] 2) The preparation method of the present invention can realize the preparation of a highly dense and highly insulating ultra-thick carbon-doped ceramic coating on the surface of metals such as titanium alloys, stainless steel, and aluminum alloys. The total thickness of the ceramic coating can reach 40 to 60 μm, and its insulation strength is 700-1100 MΩ, the bonding force is 25-40N, the hardness is 600-1000 HV, and the film layer is intact without corrosion after 3000 hours of salt spray. The ceramic coating of the present invention can take into account high density, high insulation, high bonding force, and high wear resistance;

[0026] 3) The preparation method of the present invention is simple and only requires depositing three layers on a substrate to obtain a highly dense and highly insulating ultra-thick carbon-doped ceramic coating.

[0027] The present invention also provides a highly dense and highly insulating ultra-thick carbon-doped ceramic coating, which is obtained by the above-mentioned preparation method.

[0028] The advantages of the highly dense and highly insulating ultra-thick carbon-doped ceramic coating and the preparation method of the highly dense and highly insulating ultra-thick carbon-doped ceramic coating described above over the prior art are the same and will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a structural appearance morphology diagram of the ceramic coating of Example 1 of the present invention;

[0030] Figure 2 is a cross-sectional morphology diagram of the ceramic coating of Example 1 of the present invention;

[0031] Figure 3 This is a surface morphology diagram of the ceramic coating of Example 1 of the present invention after 3000 hours of neutral salt spray corrosion test;

[0032] Figure 4 This is a surface microscopic morphology of the ceramic coating of Example 1 of the present invention;

[0033] Figure 5 This is a structural appearance morphology diagram of the ceramic coating of Example 2 of the present invention;

[0034] Figure 6 is a cross-sectional morphology diagram of the ceramic coating of Example 2 of the present invention;

[0035] Figure 7 This is a surface morphology diagram of the ceramic coating of Example 2 of the present invention after 3000 hours of neutral salt spray corrosion test;

[0036] Figure 8 This is a surface microscopic morphology of the ceramic coating of Example 2 of the present invention. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0038] The present invention prepares a carbon-doped ceramic coating on the surface of metals such as stainless steel, titanium alloy, and aluminum alloy. First, a multi-arc ion plating method is used to form a 0.2-0.8μm Ti / TiC or Cr / CrN primer layer on the surface of the substrate. Subsequently, the working gas is adjusted to argon, methane, and hydrogen, and the power and gas partial pressure are set to generate a 2-10μm carbon-based film intermediate layer. Afterwards, a sputtering process is used to simultaneously start a graphite target, an aluminum target, and a silicon target, and the working gas is adjusted to argon and oxygen, and a composite reaction is generated to generate a 10-50μm thick C / SiO2 / Al2O3 ceramic coating. The primer layer is used to improve the film-base bonding force between the ceramic film layer and the substrate, the carbon-based intermediate layer is used to improve the substrate load and as a template to force the amorphous growth of the top carbon film, and the C / SiO2 / Al2O3 ceramic coating is used to improve the insulation strength and wear resistance.

[0039] The preparation process of a highly dense and highly insulating ultra-thick carbon-doped ceramic coating of the present invention is as follows:

[0040] Step 1: Polishing and chemical cleaning: The surface of the stainless steel / titanium alloy metal parts is polished by chemical process to a surface roughness of 0.2-0.5 μm, followed by ultrasonic cleaning with acetone, anhydrous ethanol, and deionized water for 10-20 minutes, and then dried;

[0041] Step 2: Ion sputtering cleaning: Place the cleaned workpiece into the reaction chamber matrix frame and evacuate the chamber to a pressure of 1.0 to 9.0 × 10 -3 Pa, argon gas is introduced for high-energy plasma sputtering cleaning, the argon gas flow rate is 50-80sccm, argon gas is used as sputtering gas, the cleaning time is 30-40min, the sputtering chamber pressure is 0.5Pa, and the sputtering power is 600W;

[0042] Step 3: Ti / TiC, Cr / CrN bottom layer: The titanium target or chromium target is controlled by the cathode, the working gas is argon and methane or nitrogen, the argon flow rate is 30-35sccm, the methane or nitrogen flow rate is 150-175sccm, the voltage is -600~-800V, the current is 20~25A, the deposition time is 30~40min, and the transition Ti / TiC or Cr / CrN bottom layer is generated. This setting improves the bonding strength and corrosion resistance of the film layer to the substrate;

[0043] Step 4: Carbon-based intermediate layer: Turn off the titanium target or chromium target, adjust the working gas to methane, hydrogen and argon, the argon flow rate is 30-40sccm, the furnace temperature is 160-220℃, the methane flow rate is 80-120sccm, the hydrogen flow rate is 320-800sccm, the power is 1200-1600W, the bias voltage is -800--1000V, the current is 10A, the deposition time is 2-3h, and a 2-10 micron thick carbon-based intermediate layer is generated on the substrate surface. Improve the insulation strength and corrosion resistance of the substrate.

[0044] Step 5: C / SiO2 / Al2O3 ceramic surface layer: Use DC reactive sputtering process, turn on graphite target, aluminum target and silicon target at the same time, adjust the working gas to argon and oxygen, apply pulse bias of 10-20kV, pulse width of 20-30 microseconds, pulse frequency of 150-200Hz, argon working pressure of 0.3-0.5Pa, oxygen flow rate of 30-80sccm, deposition time of 10-20 hours, composite reaction to generate 10-50 micron thick C / SiO2 / Al2O3 ceramic coating.

[0045] The present invention uses a gas-phase coupled ion plating method, and the cathode arc discharge of the process has good diffraction and can ensure the uniformity of the coating film layer; the invention is suitable for the preparation of surface coatings of special-shaped parts and can break through the coating deposition in deep holes; the invention disperses and dopes a variety of insulating ceramic phases on the basis of carbon-based films, which can effectively improve the insulation of the film layer; the film layer prepared by the invention has high density, good insulation effect, and large film thickness, which can effectively avoid the problem of galvanic corrosion between dissimilar metals.

[0046] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0047] Example 1

[0048] The present invention relates to a method for preparing a highly dense and highly insulating ultra-thick carbon-doped ceramic coating, comprising the following steps:

[0049] Step 1, polishing and cleaning: The surface of the stainless steel metal parts is polished by chemical polishing process, and the surface roughness is 0.25μm, followed by ultrasonic cleaning with acetone, anhydrous ethanol, and deionized water for 10min, and then dried;

[0050] Step 2: Ion sputtering cleaning: Place the substrate cleaned in step 1 on the substrate rack of the reaction chamber in the magnetron sputtering equipment, evacuate the chamber to a pressure of 2.0×10 -3Pa, argon gas was introduced for high-energy plasma sputtering cleaning, the argon gas flow rate was 55 sccm, argon gas was used as sputtering gas, the cleaning time was 30 min, the sputtering chamber pressure was 0.5 Pa, and the sputtering power was 600 W;

[0051] Step 3, depositing Cr / CrN bottom layer: using chromium target as sputtering raw material, the chromium target is controlled by cathode, argon is used as sputtering gas, the reaction gas is nitrogen, the argon flow rate is 30sccm, the nitrogen flow rate is 160sccm, the voltage is -700V, the current is 25A, the deposition time is 30min, and a 0.3μm thick Cr / CrN bottom layer is deposited on the surface of the substrate; this setting deposits the Cr / CrN bottom layer to improve the film-base bonding strength between the ceramic surface layer and the substrate;

[0052] Step 4, depositing a carbon-based intermediate layer: turn off the chromium target, adjust the working gas to methane, hydrogen and argon, the argon flow rate is 35sccm, the furnace temperature is 200°C, the methane flow rate is 100sccm, the hydrogen flow rate is 500sccm, the power is 1500W, the bias voltage is -850V, the current is 10A, the reaction time is 2.5h, and a 3μm thick carbon-based intermediate layer is deposited on the Cr / CrN base layer; the carbon-based intermediate layer in the middle of the setting is used to improve the substrate load and as a template to force the amorphous growth of the top carbon film, thereby improving the substrate insulation strength and corrosion resistance;

[0053] Step 5. Deposition of C / SiO2 / Al2O3 ceramic surface layer: Using a DC reactive sputtering process, simultaneously turning on the graphite target, aluminum target and silicon target, adjusting the working gas to argon and oxygen, applying a pulse bias of 20 kV, a pulse width of 20 microseconds, a pulse frequency of 150 Hz, an argon working pressure of 0.4 Pa, an oxygen flow rate of 35 sccm, and a deposition time of 12 hours, a 41 μm thick C / SiO2 / Al2O3 ceramic surface layer is deposited on the carbon-based intermediate layer.

[0054] The ceramic coating prepared on the stainless steel metal part in Example 1 is as follows Figure 1 As shown; the total thickness of the ceramic coating is 43.17-45.59μm; the ceramic coating has been tested and the insulation strength is 750MΩ, the bonding force is 38N, and the hardness is 830HV; the film layer is intact and has no corrosion after 3000h of salt spray, such as Figure 3 As shown; the film structure is dense, such as Figure 4 shown.

[0055] Example 2

[0056] The present invention relates to a method for preparing a highly dense and highly insulating ultra-thick carbon-doped ceramic coating, comprising the following steps:

[0057] Step 1, polishing and cleaning: The surface of the titanium alloy metal part is polished by chemical polishing process, and the surface roughness is 0.35 μm, followed by ultrasonic cleaning with acetone, anhydrous ethanol and deionized water for 20 minutes, and then dried;

[0058] Step 2: Ion sputtering cleaning: Place the substrate cleaned in step 1 on the substrate rack of the reaction chamber in the magnetron sputtering equipment, evacuate the chamber to a pressure of 7.5×10 -3 Pa, argon gas was introduced for high-energy plasma sputtering cleaning, the argon gas flow rate was 80 sccm, argon gas was used as sputtering gas, the cleaning time was 30 min, the sputtering chamber pressure was 0.5 Pa, and the sputtering power was 600 W;

[0059] Step 3: Deposit Ti / TiC bottom layer: Use titanium target as sputtering raw material, titanium target is controlled by cathode, argon is used as sputtering gas, reaction gas is methane, argon flow rate is 35sccm, methane flow rate is 175sccm, voltage is -800V, current is 25A, deposition time is 40min, and 0.5μm thick Ti / TiC bottom layer is deposited on the substrate surface; this setting improves the bonding strength and corrosion resistance of the film layer and the substrate. In addition, the titanium carbide layer has a template effect, which can induce the amorphous growth of the carbon-based intermediate layer;

[0060] Step 4: Deposit a carbon-based intermediate layer: the working gas is adjusted to methane, hydrogen and argon, the argon flow rate is 30 sccm, the furnace temperature is 180°C, the methane flow rate is 100 sccm, the hydrogen flow rate is 700 sccm, the power is 1400 W, the bias voltage is -850 V, the current is 10 A, the reaction time is 3 h, and a 2 μm thick carbon-based intermediate layer is deposited on the Ti / TiC base layer; this setting improves the insulation strength and corrosion resistance of the substrate;

[0061] Step 5. Deposition of C / SiO2 / Al2O3 ceramic surface layer: Using a DC reactive sputtering process, simultaneously turning on the graphite target, aluminum target and silicon target, adjusting the working gas to argon and oxygen, applying a pulse bias of 12 kV, a pulse width of 25 microseconds, a pulse frequency of 200 Hz, an argon working pressure of 0.3 Pa, an oxygen flow rate of 80 sccm, and a deposition time of 20 hours, a 43 μm thick C / SiO2 / Al2O3 ceramic surface layer is deposited on the carbon-based intermediate layer.

[0062] The ceramic coating prepared on the titanium alloy component in Example 2 is as follows Figure 5 As shown; the total thickness of the ceramic coating is 43.71-46.81μm, Figure 6 As shown; the ceramic coating has been tested and found to have a dielectric strength of 800MΩ, a bonding force of 36N, and a hardness of 780HV; the film is intact and free of corrosion after 3000h of salt spray, as shown Figure 7 As shown; the film structure is dense, such as Figure 8 shown.

[0063] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing a highly dense and highly insulating ultra-thick carbon-doped ceramic coating, characterized in that: The steps include: S1. Substrate pretreatment: the pretreatment includes polishing and chemical cleaning in sequence; S2, plasma sputtering cleaning; S3, depositing a base layer; the base layer is a Ti / TiC base layer or a Cr / CrN base layer; S4, depositing a carbon-based intermediate layer on the base layer; S5. Depositing a C / SiO2 / Al2O3 ceramic surface layer on the carbon-based intermediate layer.

2. The preparation method according to claim 1, characterized in that: The thickness of the base layer is 0.2-0.8 μm, the thickness of the carbon-based intermediate layer is 2-10 μm, the thickness of the C / SiO2 / Al2O3 ceramic surface layer is 10-50 μm, and the total thickness of the ultra-thick carbon-doped ceramic coating is 45-60 μm.

3. The preparation method according to claim 1, characterized in that: Step S3 specifically comprises using a titanium target or a chromium target as a sputtering raw material, argon as a sputtering gas, and methane or nitrogen as a reaction gas to deposit a Ti / TiC primer layer or a Cr / CrN primer layer on the surface of the substrate.

4. The preparation method according to claim 3, characterized in that: In step S3, the argon flow rate is 30-35 sccm, the methane or nitrogen flow rate is 150-175 sccm, the voltage is -600 to -800 V, the current is 20 to 25 A, and the deposition time is 30 to 40 min.

5. The preparation method according to claim 1, characterized in that: Step S4 specifically includes closing the titanium target or the chromium target, using argon as a sputtering gas, methane as a reaction gas, and hydrogen as a reaction gas to deposit a carbon-based intermediate layer on the Ti / TiC base layer or the Cr / CrN base layer.

6. The preparation method according to claim 5, characterized in that: In step S4, the furnace heating temperature is 160-220°C, the methane flow rate is 80-120sccm, the hydrogen flow rate is 320-800sccm, the power is 1200-1600W, the bias voltage is -800--1000V, the current is 10A, and the deposition time is 2-3h.

7. The preparation method according to claim 1, characterized in that: Step S5 specifically comprises using graphite target, aluminum target, silicon target as sputtering raw materials, argon as sputtering gas, oxygen as reaction gas, and adopting DC reactive sputtering process to deposit C / SiO2 / Al2O3 ceramic surface layer on the carbon-based intermediate layer.

8. The preparation method according to claim 7, characterized in that: In step S5, the applied pulse bias voltage is 10-20 kV, the pulse width is 20-30 microseconds, the pulse frequency is 150-200 Hz, the argon working pressure is 0.3-0.5 Pa, the oxygen flow rate is 30-80 sccm, and the deposition time is 10-20 hours.

9. The preparation method according to claim 1, characterized in that: The surface roughness of the substrate after polishing is less than 0.5 μm.

10. A highly dense and highly insulating ultra-thick carbon-doped ceramic coating, characterized in that: The preparation method according to any one of claims 1 to 9 is used to obtain the

Citation Information

Patent Citations

  • Wolframium (W) doped diamond-like coating and preparation method thereof

    CN103451608A

  • Ceramic insulating coating and preparation method thereof

    CN112481579A

  • Insulating anti-corrosion composite ceramic coating as well as preparation method and application thereof

    CN115448705A

  • Wear-resistant high-entropy ceramic coating with nano multilayer structure and preparation method of wear-resistant high-entropy ceramic coating

    CN115725933A

  • Preparation method of insulating coating on surface of iron-based amorphous and nanocrystalline strip

    CN117344269A